Energy Consumption, Conversion, Storage, and Efficiency (IntechOpen, 2024)
Energy Consumption, Conversion, Storage, and Efficiency book presents a concise yet comprehensive exploration of energy research aimed at providing perspectives on cutting-edge technologies, storage solutions, and efficiency gains. It is a valuable source for students, professionals and a wider readership in finding reference works dealing with energy-efficient solutions for a sustainable future.